Tuberculous Otitis Media with Facial Palsy: A Case Report - Adhikari, P; Guragain, R; Bhusal, CL (Nepalese Journal of ENT Head and Neck Surgery, 2011)
DOI: 10.3126/njenthns.v1i1.4732 Nepalese J ENT Head Neck Surg Vol.1 No.1 (2010) p.17-18